Chemical Stimulation of Adherent Cells by Localized Application of Acetylcholine from a Microfluidic System - Zibek, Susanne; Hagmeyer, Britta; Stett, Alfred; Stelzle, Martin (Frontiers in Neuroengineering, 2010)
Chemical stimulation of cells is inherently cell type selective in contrast to electro-stimulation. The availability of a system for localized application of minute amounts of chemical stimulants could be useful for dose related response studies to test new compounds. It could also bring forward the development of a novel type of neuroprostheses. In an experimental setup micro-droplets of an acetylcholine solution were ejected from a fluidic microsystem and applied to the bottom of a nanoporous membrane. The solution travelled through the pores to the top of the membrane on which TE671 cells were cultivated. Calcium imaging was used to visualize cellular response with temporal and spatial resolution. Experimental demonstration of chemical stimulation for both threshold gated stimulation as well as accumulated dose response was achieved by either employing acetylcholine as chemical stimulant or applying calcein uptake, respectively. Numerical modelling and simulation of transport mechanisms involved were employed to gain a theoretical understanding of the influence of pore size, concentration of stimulant and droplet volume on the spatial-temporal distribution of stimulant and on the cellular response. Diffusion, pressure driven flow and evaporation effects were taken into account. Fast stimulation kinetic is achieved with pores of 0.82 µm diameter, whereas sustained substance delivery is obtained with nanoporous membranes. In all cases threshold concentrations ranging from 0.01 to 0.015 µM acetylcholine independent of pore size were determined.